(untitled) (Journal of Educational Sciences, 2016)
Бұл мақалада 1920-1934 жылдары Азербайджанның жалпы орта мектептерінде жағрафия пəні бағдарламасы жəңе оқыту мəселелері қарастырылған. Мақаланың авторы 1920-1934 жылдары Азербайджанның жалпы орта мектептерінде жағрафия пəні оқытудың тарихын зерттеген. In system of the basic general education geography - the unique school subject, which maintenance simultaneously covers many aspects both natural, and gumanitarno-public scientific knowledge. In article are investigated the history of teaching of geography at schools Azerbaijan in 1920-34.